Critical care medicine at a glance - Leach, Richard M. (Haematologist) (At a glance series (Oxford, England), 2014)
Critical Care Medicine at a Glance is an accessible introduction and revision text for junior clinicians. Fully revised and updated to reflect changes to the content and assessment methods used by medical schools and postgraduate training programmes, this at a Glance provides a user-friendly overview of critical care medicine to encapsulate all that the student needs to know. This new edition of Critical Care Medicine at a Glance: Is fully revised and updated to increase coverage of a rapidly expanding area of medicine